Indoor Robot Localisation with Active RFID - Wei Wei; Kevin Curran (Institute of Advanced Engineering and Science, 2012)
Radio Frequency Identification (RFID) is a technology of location determination and data capture. An RFID based system relies on the interaction between readers (also known as interrogator) and tags (transponders). Active RFID technology is suitable for tracking costly assets or moving objects such as mobile robots. Once affixed with RFID tags, a robot can be localised. However, there is a tendency for accuracy to vary greatly as well as delay in readings. Those problems may be enlarged in real time applications. This paper provides an overview of implementing RFID in precision tracking of mobile robots.DOI: http://dx.doi.org/10.11591/ijra.v1i3.487